Pelaksanaan Bimbingan Agama Dalam Mengatasi Konflik Sosial Pada Lansia di Unit Pelaksana Teknis Pelayanan Sosial Tresna Werdha Khusnul Khotimah Dinas Sosial Provinsi Riau - Listiawati; Fatmawati; Sartika Mardianti (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
Social institutions are places for the elderly to live their old age together, but it is not uncommon for conflicts to arise between residents. This conflict is triggered by mutual mockery, arrogance, stinginess, self-centeredness, suspicion, divide and conquer, and jealousy over uneven provision. This study aims to examine the implementation of religious guidance in overcoming elderly interpersonal conflicts at the Tresna Werdha Khusnul Khotimah Social Service Unit of the Riau Province Social Service. Using a qualitative method with a descriptive approach, data is collected through observation, interviews, and documentation. The results showed that religious guidance was carried out through three stages: (1) planning, which includes the preparation of schedules, materials, and methods; (2) implementation of guidance activities according to plan; and (3) evaluation, which aims to assess and improve the quality of implementation. However, this evaluation stage has not run optimally.